Production Standard and Stability of Compounded Del Nido Cardioplegia Solution. Issue 11 (December 2017) - Pereira, Luis M.; Matte, Gregory S.; Lutz, Peter; Arnold, Alana; Patterson, Al
Background: The del Nido cardioplegia solution (dNCS) was originally developed for pediatric cardiac surgery, being now also used for adult patients. Hospital pharmacies frequently resort to internal dNCS production which has led to an increase in the need for validated parameters for compounding and storage.Objective: This report defines in-house production standards, as well as the stability of dNCS under optimal storage conditions.Methods: All ingredients were sterile and United States Pharmacopeia (USP)/National Formulary (NF) certified. All final bags were quarantined at 4°C for quality control, when 3 of 33 weekly bags were randomly assayed for potassium content. Each lot was only released if all 3 samples were within ±5% of target. Stability testing was performed per USP 797 guidance. Over a 6-month period, 4 different lots and 4 bags from each lot of dNCS were assayed. Each bag was assessed for physical and chemical stability while refrigerated at 4°C, at 35°C in an incubator, and at 70°C under 80% relative humidity. A light exposure arm was also set up at 25°C under 150 lumens. Calibrators of lidocaine, mannitol, and gluconate were freshly prepared and assayed with the samples by Liquid chromatography/Mass spectrometry (LC/MS).Results: Lidocaine concentrations averaged 0.117 mg/mL (95.8% of theoretical) at 4°C for 30 days. At 35°C, they decayed by 67% in 30 days, while at 70°C nearly 50% was lost after the first day. A first-order kinetics was observed with an Arrhenius activation energy of 25 kcal/mol. Degradation products identified under stress conditions were absent in the stable product.Conclusions: The dNCS is stable for at least 30 days under 4°C refrigeration in ethylene vinyl acetate ( EVA) bags.